OP0212 Endothelin-1 induces a profibrotic phenotype in cultured human microvascular endothelial and circulating monocyte/macrophage cells. (15th June 2017) - Soldano, S; Montagna, P; Brizzolara, R; Trombetta, AC; Sulli, A; Pizzorni, C; Ghio, M; Paolino, S; Smith, V; Cutolo, M
Abstract : Background: The alteration of microvascular endothelial cell (EC) functions and the presence of macrophages in the immune inflammatory infiltrate, followed by the transition of these cell types into a profibrotic phenotype, represent early and crucial pathological features of the fibrotic process in systemic sclerosis (SSc) (1). The alternatively activated macrophage subset M2a was found in several diseases characterized by extensive fibrosis (1). M2a macrophages express specific phenotype markers, CD206 (mannose receptor), CD204 and CD163 (scavenger receptors) as well as profibrotic molecules, primarily transforming growth factor-β1 (TGFβ1) (1). Endothelin-1 (ET1) and/or TGFβ1 are known to induce the transition of fibroblasts into profibrotic myofibroblasts, which are key mediators of fibrosis in SSc. Objectives: To investigate the effects of ET1 in inducing a profibrotic phenotype in cultured human microvascular ECs (HMVECs) and macrophages. Methods: HMVECs, at 3rd culture passage, were grown in endothelial cell medium (EGM2MV) and treated for 6 days with ET1 (100nM) or treated for 1 hr with ET1 receptor antagonist (ETA/B RA, bosentan 10μM) before stimulation with ET1. Human monocytes were isolated from peripheral blood mononuclear cells of healthy subjects using a monocyte isolation kit. The cells were maintained in RPMI growth medium for 24 hrs and then treated for 6 days with ET1 or treated for 1 hr with bosentan before stimulation with ET1. Cultured HMVECs and monocytes maintained in EGM2MV and RPMI growth medium, respectively, were used as untreated cells. Gene and protein expression of profibrotic myofibroblast markers –α-smooth muscle actin (α-SMA), fibroblast specific protein-1 (S100A4), type 1 collagen (COL1) and fibronectin (FN) – were evaluated by quantitative real time polymerase chain reaction (qRT-PCR), Western blotting (WB) and immunocytochemistry (ICC) in cultured HMVECs. Gene and protein expression of M2a phenotype markers (CD206, CD204, CD163) and TGFβ1 were investigated by qRT-PCR and WB in cultured human macrophages. Statistical analysis was carried out by Mann-Whitney non-parametric test. Results: In cultured HMVECs, ET1 induced the significant upregulation of the gene expression of α-SMA, S100A4 (myofibroblast markers), COL1 and FN, compared to untreated cells (p<0.001;p<0.001;p<0.05;p<0.01). ETA/B RA significantly contrasted the ET1 mediated transition of HMVECs into a profibrotic phenotype (p<0.05 for α-SMA, COL1 and FN; p<0.01 for S100A4 vs. ET1-treated cells). In cultured human macrophages, ET1 induced the significant overexpression of M2a markers (p<0.05 for CD204 and CD163;p<0.01 for CD206) and TGFβ1 (p<0.01) compared to untreated cells. ETA/B RA significantly contrasted the ET1-mediated transition of cultured macrophages into profibrotic M2a (p<0.05 vs. ET1-treated cells, for all investigated proteins). Data were confirmed by WB and ICC on both cultured cell types. Conclusions: ET1 seems to be involved in the early phases of the fibrotic process by inducing the transition of both cultured HMVECs and macrophages into a profibrotic phenotype, myofibroblast and M2a respectively (observed in SSc), a process which is apparently contrasted by ETA/B RA treatment. References: Wynn TA et al. Immunity. 2016;44:450–62. Disclosure of Interest: S. Soldano: None declared, P. Montagna: None declared, R. Brizzolara: None declared, A. Trombetta: None declared, A. Sulli: None declared, C. Pizzorni: None declared, M. Ghio: None declared, S. Paolino: None declared, V. Smith: None declared, M. Cutolo Grant/research support from: Actelion